Izzivi sodobne varnosti - Grizold, Anton (Teorija in praksa, 2011)
The article deals with basic elements of the changing nature of contemporary security in the context of globalisation processes and fundamental changes in the security environment following the Cold War (1989/90). Within this framework, it reconsiders the response of theory and practice to the fundamental shift in traditional state behaviour from national to global security and finally to human security. Globalisation as a security challenge is dealt with through two basic approaches: (1) the neoliberal that especially stresses the role of states as key actors in the international community; and (2) the liberal-constructivist whose central elements are the relative decline of state power and the rise of the role of global social values. The article departs from the genesis of the security concept, it then deals with some new elements of the content of contemporary security and deliberates on issues of global security. It continues with human security and its origins, especially some theoretical and practical dimensions of the concept of human security. At the end, the article summarises the challenges and dilemmas of contemporary security and offers concluding remarks.
Keywords: Nacionalna varnost; National security; International security; Mednarodna varnost; Človekova varnost; Human security; Globalizacija; Globalization